Influência de configurações amostrais na qualidade de estimação espacial sob o uso de modelos espaciais bivariados - Cantu, Jacqueline Gabriela (2015)
The soil spatial variability s studies are based in geostatistics which appears as a method whose data comes from natural phenomena and consider the geographical location of the phenomenon. If in an area under study the researcher has interest in searching the variability of variables and has evidence that the steps which describe the spatial structure of this variables aren t independent a geostatistical bivariate model study can be proposed. This work concentrates on evaluating the variation s influence of the bivariate Gaussian common component model (BGCCM) parameters in calculating the Pearson correlation coefficient and analyzing the influence that sizes and sampling settings may present at the BGCCM s estimation and at spatial prediction variables in non-sampled locations. Moreover, for co-placed samples, crossed semivariograms were built and compared with univariate model and BGCCM, in relation to estimates of the model and the sizes associated with the spatial prediction. In order to do it, these methodologies were applied in simulated data sets and experimental data, from an agricultural property. The simulation study of the parameters variation influence s analysis of the bivariate model BGCCM in calculating the Pearson correlation coefficient between described variables of bivariate model BGCCM revealed that the Pearson s linear correlation coefficient can t be considered in decision-making about the presence of joint spatial dependence between pairs of variables. In the study with simulations, it was observed that the biggest differences of accuracy measures and the square sum of the spatial prediction s difference occurred when the univariate models and crossed semivariogram were compared to the BGCCM. Moreover, the simulation s study observed that for balanced data the regular and irregular meshes showed better efficiency as the spatial prediction. The study with real data showed that under the BGCCM approach, spatial dependence was observed, mainly between pH and Mn for co-placed and balanced data of the agriculture year 2010/2011; and between the variable inside of the next pairs: (Prod, RSP0-10), (Prod, RSP11-20), (Prod, RSP21-30) and (Prod, Mn) for co-placed and balanced data of the agriculture year 2013/2014; and (Prod, RSP11-20) and (Prod, RSP21-30) for co-placed and unbalanced data of the agriculture year 2013/2014. Still considering the real data study comparing the univariated models, crossed semivariogram and BGCCM, differences could be observed in the square sum of prediction s difference and in the accuracy measures, both for balanced and unbalanced data. However, considering the real data and the control sample, the spatial prediction s quality using the BGCCM model was inefficient when compared to the quality resulted from the spatial prediction using the univariate model. Nevertheless, this result may have been influenced by the choice of sample configuration.